The cider shop rules eaudiobook - Lindsey, Julie Ann (Cider Shop Mystery, 2021)
Autumn in Blossom Valley means pumpkin patches are ripe and Winona Mae Montgomery and her Granny Smythe's cider shop is flourishing. But with this season comes . . . A FATAL HARVEST The Fall Festival is in full swing. Civil War reenactors from three counties are partaking in Blossom Valley's tribute to John Brown. Blue Ridge Mountain foliage is in full bloom. And best of all is Jacob Potter's pumpkin farm where his hay rides, piglet races, pumpkin picking, and corn maze are time-honored draws for locals and tourists alike. That's why it's such a shock when Mr. Potter is found dead, hidden under a tarp in the back of Winnie's pickup truck. This certainly betrays Potter's reputation as one of the town's most popular citizens. Fortunately, when it comes to solving a murder, no one has a patch on Winnie. Now, all eyes are on her to do it. Unfortunately , that includes those of the killer who'll do anything to keep an orchard full of secrets buried.